2020
DOI: 10.1017/dmp.2020.315
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Systematic Review Exploring the Involvement of Medical Students in Pandemics and Other Global Health Emergencies

Abstract: Objectives The role of medical students in the current COVID-19 pandemic is rapidly evolving. The aim of this review is to explore the involvement of medical students in past global health emergencies, to help inform current and future scenarios. Methods A rapid systematic review was undertaken, including articles from online databases discussing the roles, willingness and appropriateness of medical student involvement in global health emergencies. Data were extracted, appraised and writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Addressing this knowledge gap will warrant not only a more effective public education but also a safer and more efficient involvement of medical students in public health emergencies beyond their role in raising public awareness. [7]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addressing this knowledge gap will warrant not only a more effective public education but also a safer and more efficient involvement of medical students in public health emergencies beyond their role in raising public awareness. [7]…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this knowledge gap will warrant not only a more effective public education but also a safer and more efficient involvement of medical students in public health emergencies beyond their role in raising public awareness. [7] One's level of knowledge is substantially influenced by an effective and efficient education system that plays a key role in ensuring high-quality teaching and learning. The low level of knowledge reported might be justified by the rapidly evolving COVID-19 evidence [26], which represents an enormous challenge to medical education and thus may subsequently hinder the delivery of educational materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of medical students in raising awareness during public health emergencies have long been established. A systematic review by Martin et al revealed that medical students have been involved in public health campaigns during previous viral outbreaks, including human immunodeficiency virus, influenza, severe acute respiratory syndrome, and Ebola [7]. Being perceived as having a higher level of health literacy, medical students may serve as role models for the public to adopt COVID-19 preventive health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students have been and continue to be on the front lines of pandemic response. For this, structured preparation, such as that provided by the sample course by Ashcroft and colleagues, is essential [28], but there must also be clearly delineated role de nitions [29].…”
Section: Introductionmentioning
confidence: 99%